Mechanisms of the TGF-β1/Smad3-signaling pathway in gender differences in alcoholic liver fibrosis - Xiaomin Hong; Sanqiang Li; Renli Luo; Mengli Yang; Junfei Wu; Shuning Chen; Siyu Zhu (Journal of Physiological Sciences)
Abstract The TGF-β1/Smad3-signaling pathway and gender differences were investigated in alcoholic liver fibrosis. Mice were divided into female normal, female model, male normal, and male model groups. Liver injury and fibrosis were assessed using histopathology and serology. Western blotting was performed to analyze the expression of relevant factors. HSC-T6 cells were divided into estradiol + saline, estradiol + ethanol, testosterone + saline, and testosterone + ethanol groups, and similar assessments were conducted in vitro. Compared with the female model group, the male model group exhibited significantly increased GPT, GOT, TNF-α, IL-6, and testosterone levels, fibrosis rate, and TGF-β1, Smad3, and PCNA expression, and significantly decreased estradiol levels and Caspase-3 expression. The apoptosis rate was higher in the estradiol + ethanol group than in the testosterone + ethanol group, although the testosterone + ethanol group exhibited significantly increased TNF-α, IL-6, Collagen-I, α-SMA, TGF-β1, Smad3, and PCNA expression, and significantly decreased Caspase-3 expression. Alcoholic liver fibrosis showed significant gender differences associated with the TGF-β1/Smad3-signaling pathway.